223k views
3 votes
I urgently need help. "Simplify the expression using trig identities. Show your steps clearly, giving a reason for each step"

I urgently need help. "Simplify the expression using trig identities. Show your-example-1
User Kumarie
by
5.3k points

1 Answer

3 votes
sin²x / tan²x

But tanx = sinx / cosx

sin²x / tan²x = (sinx / tanx)²

sinx / tanx = sinx / (sinx/cosx)

= sinx * cosx / sinx

= cosx

Therefore: sin²x / tan²x = (sinx / tanx)² = (cosx)²

= cos²x

Hope this helps.
User MathKid
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.